Performance of hydrogel and salicylic acid on productivity and economics of yellow sarson (Brassica rapa) in new alluvial zone: PERFORMANCE OF HYDROGEL AND SALICYLIC ACID ON YELLOW SARSON IN ALLUVIAL ZONE - DHIMAN MUKHERJEE (Journal of Oilseeds Research, 2024)
A field experiment was conducted under new alluvial zone to evaluate the performance of hydrogel and salicylic acid for increasing the productivity of Indian mustard in restricted irrigation condition. The experiment consisting of ten treatment combinations, viz., hydrogel @ 2.5 kg/ha, hydrogel @ 5 kg/ha, salicylic acid (SA) @ 100 ppm at flowering and siliqua formation, SA @ 200 ppm at flowering and siliqua formation, two irrigations at pre-flowering and siliqua development stage, hydrogel @ 2.5 kg/ha + SA @ 100 ppm at flowering and siliqua formation, hydrogel @ 2.5 kg/ha + SA @ 200 ppm at flowering and siliqua formation, hydrogel@ 5 kg/ha + SA @100 ppm at flowering and siliqua formation, hydrogel @ 5 kg/ha + SA @ 200 ppm at flowering and siliqua formation and control, was laid out in randomized block design with three replications. Among treatment combinations, application of hydrogel @ 5 kg/ha with two sprays of salicylic acid either 100 or 200 ppm at flowering and siliqua formation stage significantly increased various yield-attributing parameter. More seed yield obtained with two irrigation at pre-flowering and siliqua formation (1838 kg/ha) stage and showed parity with hydrogel @ 5.0 kg/ha + salicylic acid @100 ppm (1794 kg/ha) and hydrogel @2.5 kg/ha + salicylic acid @ 200 ppm (1719 kg/ha) and statistically superior to all other treatments. These treatments registered 128.6, 123.5and 113.2%, respectively, more grain yield over the control plot. Increased stover production was observed with hydrogel @2.5 kg/ha + salicylic acid @ 200 ppm and was closely followed by hydrogel @5.0 kg/ha + salicylic acid @ 200 ppm and hydrogel @2.5 kg/ha + salicylic acid @100 ppm. Furthermore, significant and highest improvement in growth, yield attributes, and economics was recorded under irrigation treatment applied at pre-flowering and siliqua formation stage over control and alone application of hydrogel and SA. Thus, the result showed that application of hydrogel either 2.5 or 5 kg/ha with two sprays of SA 100 ppm at flowering and siliqua formation was found beneficial for obtaining high seed yield as well as net returns. Application of hydrogel @ 2.5 kg/ha + salicylic acid 100 ppm at flowering stage and siliqua formation stage with maximum average benefit: cost ratio (2.66) may be recommended for mitigation of moisture stress in rainfed situations for obtaining higher crop yield in new alluvial region